E-115 Transradial versus transfemoral access for middle meningeal artery embolization for chronic subdural hematomas: propensity score-matched study. (23rd July 2022) - Salem, M; Kuybu, O; Hoang, A; Baig, A; Khorasanizadeh, M; Baker, C; Cortez, G; Hanel, R; Tanweer, O; Kan, P; Levy, E; Grandhi, R; et al.
Abstract : Introduction: Middle meningeal artery (MMA) embolization has emerged as a promising treatment option for chronic subdural hematoma (cSDH) patients. With transradial access (TRA) being more progressively utilized in neuroendovascular procedures, we sought to compare TRA versus transfemoral access (TFA) in terms of clinical and radiological outcomes. Methods: A series of consecutive patients undergoing MMA embolization for cSDH at 9 North American centers (2018–2021) were included. Patients were categorized into two groups: those who were treated with TRA or TFA. Patients' and SDH characteristics and technical/clinical outcomes were analyzed and compared between groups. All patients had follow-up imaging (i.e., ≥ 2 scans) during the following post-procedure time points: 24hours, 2 weeks, 6 weeks, and 90 days. Propensity score matching (PSM) using nearest neighbor was implemented to match groups according to the following characteristics: age, sex, concurrent surgical evacuation, history of prior surgical evacuation, maximal hematoma thickness, and midline shift both in millimeters, pre-treatment baseline platelets count and antiplatelet/anticoagulation therapy. The primary clinical endpoint was treatment failure defined as requiring additional surgical treatment within 90days of index treatment, with secondary outcomes of technical feasibility and access-related procedural complications. The primary radiological outcome was the proportion of patients with at least a 50% of reduction in maximal hematoma thickness on the last available imaging follow-up. Results: This study included a total of 538 patients undergoing 625 embolization procedures (mean age 72.3 years, 27.2% females), of which 188 (34.9%) were treated using TRA and 350 (65.1%) underwent TFA. Following PSM, 132 matched pairs were generated with similar baseline clinical and radiographic characteristics (76 in each group). There were no significant differences in treatment failures requiring rescue retreatment between the TRA and TFA groups (7.4% vs 8.9% respectively; p=0.83). Technical failures were not significantly different between TRA and TFA (0% vs 6.5% respectively; p=0.19), without procedural access-related complications encountered in either group. Concurrently, the rates of radiological improvement of ≥50% of hematoma thickness on the last imaging follow-up were similar between TRA and TFA groups (91.7% vs 75.9% respectively; p=0.13). Conclusions: TRA offers comparable outcomes to TFA in MMA embolization for cSDH in terms of clinical efficacy and radiological improvement, with similar technical feasibility and access-related complications. Disclosures: M. Salem: None. O. Kuybu: None. A. Hoang: None. A. Baig: None. M. Khorasanizadeh: None. C. Baker: None. G. Cortez: None. R. Hanel: None. O. Tanweer: None. P. Kan: None. E. Levy: None. R. Grandhi: None. B. Gross: None. A. Siddiqui: None. C. Ogilvy: None. M. Lang: None. A. Thomas: None. B. Jankowitz: None. J. Burkhardt: None.